MATHEMATICAL MODEL OF SHUNTING PROCESS AS TWO-STAGE UNRELIABLE QUEUEING SYSTEM - Michal Dorda; Dušan Teichmann (Perner’s Contacts, 2011)
The paper deals with a two-stage queuing model of the reception sidings and the hump in the marshalling yard Ostrava - Pravé nádraží. We distinguish two types of shunting - primary shunting of arriving trains we consider to be customers and secondary shunting to be system failures. By solving of the presented mathematical model some important characteristic of the modelled system are obtained.